Factor Structure and Measurement Invariance of the Teacher Reported Strengths and Difficulties Questionnaires for Elementary School Students in the United States and China - Gao, Ruiqin; Liu, Jin; Ding, Ruyi; Hardie, Suzy; He, Wei (International Journal of Applied Educational Research (IJAER), 2024)
The current study aimed to explore the factor structure and the measurement invariance of the teacher-reported Strengths and Difficulties Questionnaire (SDQ) across cultures (the United States and China). We used a sample of elementary school students in the U.S. (N=639) and China (N=666). Confirmatory factor analysis results identified the underlying 3-factor structure of the SDQ for each group sample (i.e., Internalizing Problems, Externalizing Problems, and Prosocial Behavior). A Multiple-group Confirmatory Factor Analysis indicated that SDQ showed full configural, metric, scalar, and residual invariance across the U.S. and China within the elementary school setting. The present study’s findings contributed to the literature by adding additional validity evidence of teacher-reported SDQ, supporting the feasibility of cross-cultural comparisons of elementary school children’s mental health measured by teacher-reported SDQ.